2006
DOI: 10.1038/sj.emboj.7601285
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinases interacting kinases are autoinhibited by a reprogrammed activation segment

Abstract: Autoinhibition is a recurring mode of protein kinase regulation and can be based on diverse molecular mechanisms. Here, we show by crystal structure analysis, nuclear magnetic resonance (NMR)-based nucleotide affinity studies and rational mutagenesis that nonphosphorylated mitogen-activated protein (MAP) kinases interacting kinase (Mnk) 1 is autoinhibited by conversion of the activation segment into an autoinhibitory module. In a Mnk1 crystal structure, the activation segment is repositioned via a Mnk-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 56 publications
0
88
0
Order By: Relevance
“…Previous work has suggested that Mnk-inducible phosphorylation of eIF4E is important in the control of cap-dependent translation and protein synthesis in other cellular systems (30)(31)(32), and there is evidence that such phosphorylation promotes HSV-1 mRNA translation and replication (33), and cytokine (TNF␣) biosynthesis (28,29). However, it appears that under certain conditions, Mnk kinases exhibit negative effects on protein translation and synthesis (34,35), while there is evidence for a unique Mnk-regulatory mechanism that involves conversion of the activation segment into an autoinhibitory module (36). It is possible that such an auto-inhibitory mechanism may explain the diversity of responses seen in response to Mnk kinases in different systems, but this remains to be directly established in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has suggested that Mnk-inducible phosphorylation of eIF4E is important in the control of cap-dependent translation and protein synthesis in other cellular systems (30)(31)(32), and there is evidence that such phosphorylation promotes HSV-1 mRNA translation and replication (33), and cytokine (TNF␣) biosynthesis (28,29). However, it appears that under certain conditions, Mnk kinases exhibit negative effects on protein translation and synthesis (34,35), while there is evidence for a unique Mnk-regulatory mechanism that involves conversion of the activation segment into an autoinhibitory module (36). It is possible that such an auto-inhibitory mechanism may explain the diversity of responses seen in response to Mnk kinases in different systems, but this remains to be directly established in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Two unusual features of the catalytic domains of the Mnks are the presence of (i) a DFD rather than the 'canonical' DFG motif in sub-domain VII and (ii) a short insert (EVFTD in Mnk1) between sub-domains VIII and IX [14]. The crystal structure suggested that the phenylalanine residue of the insert (F230 in hMnk1a) prevents the DFD motif from forming the 'DFG/D-in' conformation which allows ATP binding [13;14].…”
Section: Residues In the Catalytic Domain Of Mnk1 Influence Its Activmentioning
confidence: 99%
“…Recent structural studies of the catalytic domains of the Mnks revealed residues which may play a role in determining their properties, including the differences between Mnk1 and Mnk2 [13;14], thereby prompting questions about the role of the specific conserved residues which differ between these domains of Mnk1 and Mnk2. A c c e p t e d M a n u s c r i p t Licenced copy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of the A-loop can break such interactions and activate a kinase, as seen for Mnk1 [52]. MSK1 disrupts its active conformation by trapping its A-loop in a b-sheet involving the N-terminus and the pre-helix aC segment [53].…”
Section: Keeping Kinases Inactivementioning
confidence: 99%